Vibrio vulnificus specie isolation in series blood culture. A case report. - Elio Jesús Núñez Tamayo; Susana Chamero Melgarejo; Julián Viera Yanez; Belkys Rodríguez Llerena; Nancy Ramírez Martínez; Dania Peñaranda Pordomingo; Annia Alvarado Borges (Medisur)
This papers contains a report of a case with Vibrio vulnificuls, gram negative micro organism that ferments carbohydrates and that is positive to the oxidase test and halophile in a patient with history of heart and liver disease who was assisted at the Intensive Care Emergency Unit ( ICU )of the ¨Dr. Gustavo Aldereguía Lima¨ University Hospital in July 2003. Thy symptoms were: oedema in lower limbs, orthopnea, chest pain that was interpreted as a case of pneumonia and a Myocardial Infarction. This patient progresses rapidly to cardiac arrest, is reanimated , and is admitted at the ICU with control pressuremetric ventilation. Vibrio Vulnificuls was isolated with a conventional diagnosis from hemo cultures. Anti microbial Susceptibility tests , the micro organism was susceptible to tetracycline, sulphaprim, aztreonam, ampicillin and was resistant to chloranphenicol.